ARABIC LANGUAGE DIRECTIVE SPEECH ACT IN SALAHUDDIN AL-AYYUBI MOVIE - Rahmawati, Nailur; Irawati, Retno Purnama; Nawawi, Muchlisin; Sulimah, Sulimah (IMLA (Arabic Teacher and Lecturer Association of Indonesia), 2020)
A movie can be used as an effective and feasible medium for delivering messages; this served as the study’s rationale. This research acquired communicative speeches in the Salahuddin Al Ayyubi movie. This research aimed to explore two objectives: to describe the form of directive speech acts and to find out the functions of the directive speech acts. The techniques used in this research comprised: (1) uninvolved conversation observation; (2) recording; (3) transcription; and (4) note-taking. The results showed that (1) there were six forms of directive speech acts in the dialogues of